Green supply chain decision of discarded drugs recycling: Evolutionary game and strategy simulation - Wang, Chao; Huang, Zhe; Lian, Guiyu (PloS one, 2023)
The research on the recycling of discarded drugs has become an important direction of the green supply chain in China. Faced with the great challenge of recycling discarded drugs in China, it is necessary to make clear the behavior choice of each recycling subject. This paper constructs an evolutionary game model among government, drugs recycling companies and consumers, describes the evolutionary game process, and analyzes the influence of the gain of government, drug recycling enterprises and consumers on the evolutionary stable strategy trend. By using Matlab simulation software to simulate the evolution of tripartite behavior, the final result is obtained: The government’s choice of a strong regulatory strategy has an important positive role in guiding the entire discarded drug recovery market. Consumer’s choice of active participation strategy and enterprise’s choice of active participation strategy are most beneficial to the healthy development of the discarded drug recovery market. This study provides some valuable theoretical support and reference for the national decision-making of discarded drug recovery, helps to solve the problem of discarded drug recovery, and provides theoretical support and policy-making recommendations for the ultimate achievement of sustainable development goals.